Rethinking large group lectures – how far in this format - ERZİK, CAN; GÜLPINAR, MEHMET ALİ; YEGEN, BERRAK (My University, 2022)
Objective: The aim of this study is to determine the perceptions, attitudes, and behaviour of medical students and lecturers regarding the lectures and their effects on students’ learning behaviour.Materials and Methods: This was a qualitative study including multi-methods. Researchers observed lecture ambiance and activities in two courses. Lectures were observed and slide-presentations were evaluated. Additionally, in-depth and focus group interviews were conducted.Results: Two researchers attended and observed 75 lectures. The average number of attendees was 51.21. Eighty percent of lecturers did not introduce any activities to attract attention and prepare students for the lecture. Only 12% of lectures were taught interactively. Of the evaluated 43 (69.80%) slide-presentations, sufficient association or integration was not made between clinical and basic sciences.Conclusion: This study revealed that the lectures created negative feelings and thoughts in students and lecturers, and led to undesirable attitudes and behaviour. It is essential to focus on giving interactive lectures which aim at developing reasoning, decisionmaking, and evaluation competencies. The most significant factors determining students’ attendance and appraisal of the lectures were related to the preparation of the lecturers, the intensity of the content, integration between basic science and clinical science, and the presentation skills.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Tıp Eğitimi; Medicine; Health Sciences; Fundamental Medical Sciences; Medicine Education; Klinik Tıp (MED); Klinik Tıp; TIBBİ ETİK; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL ETHICS; MEDICINE, GENERAL & INTERNAL; Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Integration; Lectures; Medical education; Undergraduate; Teaching methods